(untitled) (Global Journal of Medical Research, 2023)
Globally there have been attempts towards improving the coverage of malaria preventive measures with the 2015 goal of the World Health Organization s WHO s Roll Back Malaria Partnership centered to reduce global malaria cases by 75 and to reduce malaria deaths to near zero through universal coverage by effective prevention and treatment interventions Regrettably malaria still constitutes a serious public health problem in Nigeria The aim of this study was to assess long lasting insecticide treated net use among women of child bearing age in Nwangele LGA Imo State A community based descriptive cross sectional study was used for the study The study involved women of child bearing age aged 15-45yrs at Nwangele LGA as its Target Population A Probability based multi stage sampling method was adopted for the study A semi-structured questionnaire was used as the instrument of data collection for this study and Statistical Package for the Social Sciences SPSS was used in the analysis of the data gotten from the study A total of 404 women participated in the study